"AUTOMATING ECONOMIC ISSUES: THE EXAMPLE OF AUTOMATING WAREHOUSE PRODUCT STORAGE ACCOUNTING AND ITS SOFTWARE" (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
The automation of warehouse product storage accounting represents a transformative approach to addressing economic issues within businesses. By implementing specialized software, companies can streamline inventory management, reduce operational costs, and enhance overall efficiency. This automation facilitates real-time tracking, minimizes human error, and allows for timely decision-making based on accurate data analysis. As a result, businesses are better equipped to respond to market fluctuations and customer demands, leading to improved profitability and competitiveness. Ultimately, automating these processes not only optimizes individual operations but also contributes to the stability and growth of the broader economic landscape.
Keywords: Warehouse logistics; warehouse management; warehouse accounting; information system; clients; equipment; personnel; storage locations